Los retos intertextuales de la novela la balada del pajarillo de Germán Espinosa (2020)
The thesis addresses the analysis of the novel la Balada del pajarillo (2000) by the colombian writer Germán Espinosa (1938-2007). The novel in question is a work that challenges the reader within the field of Arts and Humanities. In the introduction to this research the author Germán Espinosa, his varied work and the academic corpus that his literature has generated are contextualized. The state of the art is also mentioned, and the justification for preparing a study that expands on what has already been said about la Balada del pajarillo. Hence, the approach to the research problem is the following: what are the intertextual challenges that the reader of la Balada del pajarillo must overcome to appreciate the wide network of communicating vessels that Germán Espinosa's novel proposes. This problem is developed in two chapters; the first, focused on analyzing the paratextual elements: the title, the front page, the back cover review, the dedication, the index and the epigraphs; and the second chapter focused on developing the way intertextuality is the central nucleus of the narrative matter. In addition, it resorts to the conceptualization, and later exemplification, of the term ekphrasis whose more general meaning is the verbal representation of a pictorial work. In La balada del pajarillo, the different exercises in ekphrasis constitute the center of the drama, and the verbal description of various pictorial works is largely the motivation to establish different dialogues between the main and secondary characters. In the end, it is concluded that intertextuality is an inherent element in Germán Espinosa's novel, an aspect that brings various areas of human knowledge into dialogue.